2007
DOI: 10.1902/jop.2007.070146
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Intrabony Defects Using Guided Tissue Regeneration and Autogenous Spongiosa Alone or Combined With Hydroxyapatite/β‐Tricalcium Phosphate Bone Substitute or Bovine‐Derived Xenograft

Abstract: The combined use of ASB with BDX or HA/beta-TCP led to significantly greater gain of clinical attachment and hard tissue formation compared to the use of ASB alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
60
2
7

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(70 citation statements)
references
References 42 publications
1
60
2
7
Order By: Relevance
“…These results are, however, in contrast to the study reported by Zafiropoulos et al (30), which demonstrated that the use of a composite autogenous-alloplast graft with a bioabsorbable membrane led to significantly greater gain of clinical attachment and hard tissue formation compared to that observed with autogenous bone grafts alone with membrane. However, it should also be noted that the study was non-randomized, included smokers and the preoperative probing depths were not taken into consideration.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…These results are, however, in contrast to the study reported by Zafiropoulos et al (30), which demonstrated that the use of a composite autogenous-alloplast graft with a bioabsorbable membrane led to significantly greater gain of clinical attachment and hard tissue formation compared to that observed with autogenous bone grafts alone with membrane. However, it should also be noted that the study was non-randomized, included smokers and the preoperative probing depths were not taken into consideration.…”
Section: Discussioncontrasting
confidence: 95%
“…Bioactive glass has also been successfully used as a composite graft with autogenous bone in sinus lift procedures (33,34). Limited clinical data exist on the use of composite grafts in the treatment of periodontal intrabony defects (30,32). In the present study, the clinical attachment gain observed with the two test groups was not significantly different, suggesting that autogenous bone can be mixed with bioactive glass if the amount of the harvested bone is not sufficient.…”
Section: Discussionmentioning
confidence: 99%
“…The osteoconductive capability of the composite HA/β‐TCP bone substitute has been shown previously in maxillary sinus elevation and periodontal regeneration studies 42,43 . However, in this regard, heterogeneous results were shown by randomized clinical trials comparing the clinical outcomes produced by EMD, alone or in combination with various bone fillers.…”
Section: Discussionmentioning
confidence: 81%
“…In a previous study by Zafiropoulos et al [32], it was reported that applying BCP resulted in a significantly greater gain of clinical attachment and hard tissue formation using the combination of autogenous bone with BCP. Research has shown that applying novel biphasic calcium composite (BCC) grafting material comprised of a porous β-TCP and calcium sulfate phase to IBDs, the clinical benefits of BCC were similar to those of autogenous bone, but it has also shown improved results when compared to OFD alone [33].…”
Section: Discussionmentioning
confidence: 99%